An assessment of multi-scale models based on second-order computational homogenisation. (15th January 2022) - Rodrigues Lopes, Igor A.; Andrade Pires, Francisco M.
Highlights: Different models based on second-order computational homogenisation are examined. The underlying formulations are reviewed and subjected to a comparative discussion. Numerical results for homogeneous RVEs are validated against an analytical solution. Extensive numerical experiments are performed to assess the response of the models. The capability to predict size effects is explored through FE 2 simulations. Abstract: Multi-scale formulations that combine a macro-scale second gradient theory with the classical continuum at the micro-scale are examined in this contribution. In particular, the homogenisation formulations proposed by Kouznetsova et al. (2002), Luscher (2010), Blanco et al. (2016) and Rodrigues Lopes and Andrade Pires (2021) are reviewed and compared. A comprehensive analysis of the underlying micro-scale constraints for each formulation is undertaken and their impact on the predictive capability is investigated. Remarkably, the formulations proposed by Luscher (2010) and Rodrigues Lopes and Andrade Pires (2021) are equivalent, despite their different initial assumptions. The formulations based on Kouznetsova et al. (2002) may suffer from spurious localisation and mesh dependency in the numerical results at the RVE level as a consequence of the lack of a volumetric constraint. The minimal constraint proposed by Blanco et al. (2016) results in an over constraint that causes a non-physical warping near the RVE corners and edges. Interestingly, an FE 2 simulation of the boundary shear layer problem reveals that the macroscopic length scale parameter is independent of the multi-scale formulation.